2022
DOI: 10.1055/s-0042-1757946
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Aortic Injury due to Broken Ribs and Preventive Measures

Abstract: We herein report two cases of patients that underwent prophylactic operations to prevent aortic injuries in association with fractured ribs. Penetrating aortic injuries induced by fractured ribs remain fatal. Prophylactic operations appear effective. However, the indication for such operations should be clarified further in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…With regard to reports of delayed perforated aortic injury, previous reports have described cases where late displacement of rib fractures occurred in conjunction with a flail chest near the descending aorta, leading to aortic perforation and resulting in a fatal outcome. [ 4 ] Although the instability of the chest wall was not confirmed in the present case, the proximity of the enlarged ascending aorta to the sternal fracture due to aging and hypertension, along with the possibility of the aorta being subject to movement during its own pulsation,[ 5 ] may have contributed to the delayed aortic injury. Furthermore, considering the potential movement of the thoracic cage during activities like handwashing after using the restroom, it is plausible that such movements could have caused the delayed aortic injury.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…With regard to reports of delayed perforated aortic injury, previous reports have described cases where late displacement of rib fractures occurred in conjunction with a flail chest near the descending aorta, leading to aortic perforation and resulting in a fatal outcome. [ 4 ] Although the instability of the chest wall was not confirmed in the present case, the proximity of the enlarged ascending aorta to the sternal fracture due to aging and hypertension, along with the possibility of the aorta being subject to movement during its own pulsation,[ 5 ] may have contributed to the delayed aortic injury. Furthermore, considering the potential movement of the thoracic cage during activities like handwashing after using the restroom, it is plausible that such movements could have caused the delayed aortic injury.…”
mentioning
confidence: 85%
“…To prevent occurrences such as this case, it is suggested that measures such as prefixation of the sternal fracture site and/or removal of sharp objects could be considered to enhance safety. [ 4 ]…”
mentioning
confidence: 99%